Interactive guiding and localization platform - Ramos, João Ricardo Martins (2014)
Technology is now part of everyone’s life, being widespread and present in the most innocuous objects, making people able to benefit from several technological solutions that only a few years ago were impossible to be implemented. For instance, the smartphone is one example of this type of technology. Usually, this device is equipped with several sensors and a GPS module, which may be used as an orientation system when it carries the right features. The current trend is providing advanced applications to the common public, excluding some fringes of the population, like the people with cognitive disabilities. Thus, everyday technology can be used for helping on several tasks, becoming an interactive terminal, aware of the user conditions. There may be orientation applications that are too complex to be used by people with cognitive disabilities. Therefore, the main goal of this work is to build and implement an orientation method that may be used by people with mild cognitive disabilities and provides several tools to the caregivers. Furthermore, the system is linked to external services like iGenda so the user is stimulated to go outside and increase his/her social participation or not to miss an appointment. The developed system is also a localization system, enabling caregivers to know in real-time the location of the person with cognitive disabilities. Allowing the user to have an independent life.